Data from: Interspecific Y chromosome variation is sufficient to rescue hybrid male sterility and is influenced by the grandparental origin of the chromosomes - Araripe, Luciana O.; Tao, Yun; Lemos, Bernardo (Dryad, 2016)
Y chromosomes display population variation within and between species.
Co-evolution within populations is expected to produce adaptive
interactions between Y chromosomes and the rest of the genome. One
consequence is that Y chromosomes from disparate populations could disrupt
harmonious interactions between co-evolved genetic elements and result in
reduced male fertility, sterility or inviability. Here we address the
contribution of ‘heterospecific Y chromosomes’ to fertility in hybrid
males carrying a homozygous region of Drosophila mauritiana introgressed
in the Drosophila simulans background. In order to detect Y
chromosome–autosome interactions, which may go unnoticed in a
single-species background of autosomes, we constructed hybrid genotypes
involving three sister species: Drosophila simulans, D. mauritiana, and D.
sechellia. These engineered strains varied due to: (i) species origin of
the Y chromosome (D. simulans or D. sechellia); (ii) location of the
introgressed D. mauritiana segment on the D. simulans third chromosome,
and (iii) grandparental genomic background (three genotypes of D.
simulans). We find complex interactions between the species origin of the
Y chromosome, the identity of the D. mauritiana segment and the
grandparental genetic background donating the chromosomes. Unexpectedly,
the interaction of the Y chromosome and one segment of D. mauritiana
drastically reduced fertility in the presence of Ysim, whereas the
fertility is partially rescued by the Y chromosome of D. sechellia when it
descends from a specific grandparental genotype. The restoration of
fertility occurs in spite of an autosomal and X-linked genome that is
mostly of D. simulans origin. These results illustrate the multifactorial
basis of genetic interactions involving the Y chromosome. Our study
supports the hypothesis that the Y chromosome can contribute significantly
to the evolution of reproductive isolation and highlights the conditional
manifestation of infertility in specific genotypic combinations.
RAW DATA final experimentExcel table with progeny numbers from males of
each combination of ancestral background, homozygote introgression and Y
chromosome origin. These were the raw data used in the statistical
comparisons.